HUBUNGAN KARAKTERISTIK KADER KESEHATAN TERHADAP KUNJUNGAN PASIEN DALAM PENCEGAHAN PENULARAN TUBERKULOSIS PARU - Asriwati Amirah; Ketut Suarayasa; Herry Imran; Patrice Armando Sipayung (Media Penelitian dan Pengembangan Kesehatan, 2022)
One effort to increase visits to pulmonary tuberculosis patients is by finding cases and tracking officers by increasing the role of cadres. The study aimed the relationship of health cadre characteristics to patient visits in preventing pulmonary tuberculosis transmission. In order to examine the relationship between cadre activity factors and tuberkulosis paru patient visits in the prevention and transmission of tuberkulosis paru disease, this type of research employs cross-sectional methodology and quantitative research methods. The population in this study was 110 cadres at the Panombeian Panei Community Health Center. The sampling technique used in this study was a total sampling technique. The research sample consisted of 110 cadres. The bivariate test uses the Chi-Square Test. The results of the study showed that there was a relationship between knowledge (0.003), attitude (0.002), and visits by pulmonary tuberkulosis paru patients. knowledge, attitudes, and activities of cadres influence pulmonary tuberkulosis paru patient visits. It is recommended that cadres continue to be given training and an in-depth understanding of pulmonary tuberkulosis paru, including how to treat and prevent it. Apart from that, it is also important to encourage cadres to have a positive and empathetic attitude towards pulmonary tuberkulosis paru patients, so that they can provide optimal support during patient visits.